Perancangan Front End Pemeriksaan dan Perawatan Wesel dengan Metode User Centered Design - Edoardus Dwijo Wijayanto; Hutanti Setyodewi (JURIKOM (Jurnal Riset Komputer), 2023)
In the era of globalization like now the website becomes very important to spread information or to store data. The internet is one of the tools to spread information that is easy and fast because it can be done anywhere and anytime. With the existence of the internet and websites can be used to store data inspection and note maintenance. At present the Indonesian railroad company is still reporting the results of the inspection and maintenance of the letter of notes manually, making it difficult to find inspection and maintenance information when the supervisor of the railroad company needs to conduct an inspection. The purpose of this research is to build an information system or website inspection and maintenance website (sell maintenance) so that it makes it easier for railroad company employees to store inspection and note maintenance data so that the data becomes more structured. Making a system or website is done by collecting data through Wawan Ways, Observation and Literature Review. Creating the Sell Maintenance website uses the User Centered Design method by applying the PHP programming language and using the Bootstrap framework to make the display more attractive. The result of this study is a website that suits the needs and preferences of users so that it is easier to use and intuitive because in this study conduct direct observations and interactions with users to understand how users use these products or services. In this study after testing the railroad company employees it was found that the presentation font in the reporting status display was changed to make it greater, the notes photo in the asset data display was changed to be smaller so that it was not too much scroll down, the header and footer on the printed display were removed, The font size on the print display is reduced, the size of the photo pixel and the layout are repaired so that they are not too many pages